Early childhood development and family adaptation during the COVID‐19 pandemic: A mixed methods study - Quezada Ugalde, Ana María (2025)
The COVID‐19 pandemic caused significant disruptions in daily life. This mixed‐methods study aimed to connect the developmental levels of children aged 1–3 years in 2020–2021 who grew up during the pandemic with their families' adaptation experiences, providing a comprehensive understanding of child development. The quantitative phase included 183 children, while 18 families participated in qualitative interviews. Quantitative results revealed delays in children's overall development, particularly in fine motor skills. Qualitative findings highlighted the coping strategies parents employed to navigate new challenges. Sequential integration analysis showed that parents prioritized meeting basic needs but faced obstacles such as limited time, lack of knowledge, and insufficient professional guidance, which restricted opportunities for early learning and provide enriching environments for child development. This mixed‐methods research shed light on the developmental risks faced by children in two underexplored Latin American contexts.